Service excellence in the light of cultural diversity: the impact of metacognitive cultural intelligence. Issue 2 (13th March 2017) - Lorenz, Melanie P.; Ramsey, Jase R.; Tariq, Ayesha; Morrell, Daniel L.
Abstract : Purpose: The purpose of this paper is to understand when, how, and why service employees adapt the service encounter to meet the values and expectations of culturally disparate customers. Design/methodology/approach: The authors tested the hypothesized framework utilizing a scenario-based experimental study. In total, a sample of 296 prospective restaurant service employees were asked to evaluate their willingness to adapt their behavior when faced with cultural differences as well as out group status. Furthermore, respondents were asked to assess their level of metacognitive cultural intelligence. Findings: The authors found that both perceived cultural differences and out group status positively affect the service employee's willingness to adapt their behavior. Further, cultural intelligence (CQ) positively moderates one of those two direct relationships. Originality/value: The authors extend the literature on the service-adjustment process, as well as the managerial implications of service adjustment. The study is among the first to introduce the role of the service employees' CQ in adaptation to an intercultural service encounter.